Topping and NPK fertilization alter seed germination, plant growth and active components of Valeriana amurensis - Wu, Junkai; Leng, Dayong; Huo, Jinhai; Zhang, Ruoquan; Du, Xiaowei (Frontiers in Plant Science, 2024)
Valeriana amurensis, a tall herbaceous plant, has been traditionally utilized as a herbal remedy both in China and Russia. This study was set to explore how to cultivate high quality seedlings, considering factors such as seedling time, seeding density, shading, and plastic film mulching. In addition, we investigated the impact of topping and fertiliser on the growth and quality of V. amurensis. According to the percentage of seed germination, the seeds of V. amurensis were sowed with 0.88 g m -2 density using plastic film mulching from late April to mid-May (germination percentage was more than 30%). The optimal Transplanting time was identified as late September, ensuring a high survival rate of 98%. Generally, topping showed the most improved growth indices in late fruit period (21.87 for number of radical leaves) and withering period (6.50 for number of buds and 234.81 for number of roots). Topping increased the yields of valtrate (10.91 mg per plant), valepotriates (809.51 mg per plant) and essential oil (395.64 mg per plant) in withering period.Nitrogen fertiliser promoted maximum root growth and increased the biomass of V. amurensis.Meanwhile, N fertilizer significantly increased the yields of valtrate to 10.46 mg per plant and valepotriates to 772.32 mg per plant among three types of fertilisers. Seedlings are obtained according to rational sowing factors and transplanting time. Topping and nitrogen fertilization emerge as superior strategies to enhance the growth and medicinal quality of this valuable plant. This study provides actionable insights for the cultivation V. amurensis.